Afwesigheid van God en teenwoordigheid van "god(e)" in Hooglied - Viviers, Hennie (HTS teologiese studies, 2008)
The absence of and the presence of “god(s)” in the Song of Songs The absence of the Israelite God in the Song of Songs is conspicuous. The poet of the Song is far too sophisticated to attribute this to a slip of the mind. Among many reasons offered for the absence of Israel’s societal stereotype of God, might the Song’s alternative views on gender relations, within a love setting, perhaps be a reason for prohibiting the “ultimate Patriarch” to interfere? Interestingly the Song contains quite a number of other notions of counter- intuitivity (= gods) confirming humans’ propensity, since early evolution, to create gods to fulfil certain needs. Although it is an ancient love-song the Song has much to offer on gender and god constructs and the implications thereof for the civilization of society today.